Italiaanse renaissanceschilderkunst - Zuffi, Stefano; De Rynck, Patrick; Darbé, Sandra ([Antwerpen] : Ludion, 2010)
Inleidend overzicht in woord en beeld van de Italiaanse schilderkunst in de 15e en 16e eeuw
boek